WIND ENERGY – ECOSUSTAINABILITY ENGINEERING SOLUTION - Roxana Gabriela POPA; Maria CALINOIU (Fiabilitate şi Durabilitate)
Renewables provides increased safety energy supply and limiting imports of energy resources, interms of sustainable economic development. The new requirements for sustainable development have determinedthe world to put the issue of energy production methods and increase the share of energy produced fromrenewable energy. This paper presents the history of wind power, advantages and disadvantages of renewableenergy, particularly wind energy as an alternative source of energy. Windmills can be horizontal axis or verticalaxis Savonius and Darrieus rotor. Latest innovations allow operation of variable speed wind turbines, or turbinespeed control based on wind speed. Wind energy is considered one of the most sustainable choices betweenvariants future wind resources are immense.